Water issues in Malaysia - Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2021)
Malaysia has one of the highest rates in population access to tap water. Based on 2017 data, Malaysia extracts 18.375 billion liters of raw water per day for treated water supply alone. However, water issues are still a significant problem in Malaysia. The aims of this paper was to highlight the water issues in Malaysia. Secondary data are collected with regard to “water issues” scope matters. River pollution, the safety of drinking water, and water disruption are some of the related water issues in Malaysia. These issues are connected. Polluted rivers caused water disruption and deterioration of drinking water quality. Undoubtedly, the water problem that we face nowadays is because we failed to see water as scarce commodities and partly due to the mismanagement of the finite water resource that we have taken for granted. The problem arising is not an easy one to solve. All these problems caused great inconvenience to the public. In short, many challenges have come up to create better water governance in Malaysia. Water is on people’s life business and responsibility, reaching from the government to water corporations, water companies, water authorities, businesses, consultants, NGOs, industries, and the citizenry. Thus, an integrated approach plan involving all stakeholders, including community participation, to cultivate the sense of ownership should be established and implemented.